Enacting a Task-Based Language Teaching Curriculum in Indonesian non-Formal Education (INFE): Rationales and Challenges - M. Junaidi Marzuki (EDULANGUE, 2022)
Tasks-Based Language Teaching (TBLT) has successfully attracted attention of a second (L2)/foreign language (FL) practitioners, researchers, trainers as well as curriculum developer. Much of the research conducted, however, has mainly focused in formal educational settings, and less research carried out in non-formal educational context.  The intent of this paper, therefore, is to advocate the notion of enacting TBLT curriculum in General English (GE) program in the pursuit of increasing students’ language communicative competence at Institute of English Course and Training (IECT), one of Indonesian Non-Formal Educations (INFE) in East Lombok Regency of Nusa Tenggara Barat Province, Indonesia. The rationales and challenges of enactment will be provided, and mainly will be based on my experience as a founder of non-formal language centers, as well as a reflexive practitioner. The advocacy should not solely confine to my home regency, East Lombok, but also to language center of INFE that runs GE in Nusa Tenggara Province.